Bankruptcy Procedures for Sovereigns : A History of Ideas, 1976-2001 - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper ;, 2002)
This paper describes the evolution of ideas to apply bankruptcy reorganization principles to sovereign debt crises. Our focus is on policy proposals between the late 1970s and Anne Krueger's (2001) proposed "Sovereign Debt-Restructuring Mechanism," with brief reference to the economics literature on sovereign debt. We describe the perceived inefficiencies that motivate proposals, and how proposals seek to change debtor and creditor incentives. We find that there has been a moving concensus on what constitutes the underlying problem, but not on how to fix it. The range of proposed approaches remains broad and only recently shows some signs of narrowing.